Neither Compatriots Nor Refugees: Status Discrimination Of Exiled Tibetans And The Contradictory Faces Of The Republic Of China (Taiwan) - Mei, Lin (Penerbit Universiti Sains Malaysia (USM Press), 2015)
This article focuses on the double liminality that exiled Tibetans face in Taiwan today. In the context of the international political system, refugees or stateless people cannot be placed into any existing order of nation-states. Refugees are in a state of liminality. With its national title "Republic of China" (ROC), Taiwan has been placed in an ambiguous position with its status as neither a nation-state nor a non-nation-state ever since the ROC was expelled from the United Nations. The ROC is in a state of liminality among states in the international order. In addition, Taiwan claims its sovereignty over Tibet, despite losing this sovereignty in 1949 to the communists. Taiwan's ambiguity of identity pushes the government neither to treat Tibetan refugees in Taiwan as compatriots nor accept their status as refugees. Placed under double liminal status, exiled Tibetan refugees in Taiwan have been discriminated against and denied their entitled human rights. This paper provides two cases to reveal the very real difficulty of their situation in Taiwan. Both stories present the kind of dilemma the exiled Tibetans face in Taiwan due to this double liminality